Pengaruh Pemberian Reward dan Punishment Terhadap Disiplin Belajar PAI Siswa SMK Negeri 1 Baso - Saiful Yeri; Darmiwanti Darmiwanti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractGiving prizes and Punishment is a way to increase learning discipline, this research how big the influence of givng prizes and Punishment is on the PAI learning discipline of students at SMK Negeri 1 baso. The type of research with descriptive coreelative research methods. The data collelection technique in this research used a questionnaire. The research subjects werw 60 students of SMK Negeri 1 Baso. The results of this research are as follows: the score for giving gifts was 79,28 in the high category, the score for giving Punishment was 78,22 un the high category dan the learning discipline score was 81,89 in the very high category, while the score for the influence of giving gifts on learning discipline was 0,652 in the strong category, the influence score giving Punishment for discipline is 0,498 in the sufficient category and the score for the influence of giving gitfs and Punishment for learning disciplne is 0,665 in the strong category. This research concludes that discipline can be realized in the learning process by applying the method of giving gifts and giving Punishment, and the suggestion that can be made is that teachers are expected to be more innovative and creative ib creating and implementing giving gifts and Punishment. Students are expected to remain disciplined and study hard. AbstrakPemberian Reward dan punishment merupakan cara untuk meningkatkan kedisiplinan belajar, penelitian ini membahas tentang seberapa besar pengaruh pemberian Reward dan Punishment terhadap disiplin belajar PAI siswa SMK Negeri 1 Baso, jenis penelitian yang dipakai adalah penelitian kuantitatif dengan metode penelitian deskriptif korelatif. Teknik pengumpulan data dalam penelitian ini menggunakan angket. Subjek penelitian adalah 60 siswa SMK Negeri 1 Baso. Hasil penelitian ini adalah sebagai berikut: skor untuk pemberian reward sebesar79,28 pada kategori tinggi, skor pemberian punishment sebesar 78,22 pada kategori tinggi dan skor disiplin belajar sebesar 81,89 pada kategori sangat tinggi, sedangkan skor pengaruh pemberian reward terhadap disiplin belajar sebesar 0,652 pada kategori kuat, skor pengaruh pemberian konseksuensi terhadap disiplin sebesar 0,498 pada kategori cukup dan skor pengaruh pemberian reward dan konseksuensi terhadap disiplin belajar sebesar 0,665 pada kategori kuat. Penelitian ini menyimpulkan bahwa kedisiplinan dapat terwujud pada proses pembelajaran dengan menerapkan metode pemberian reward dan pemberian punishment, dan saran yang dapat di sampaikan adalah guru diharapkan lebih inovatif dan kreatif menciptakan dan menerapkan pemberian reward dan konseksuensi. Bagi siswa diharapkan tetap disiplin dan giat giat belajar